2016
DOI: 10.1007/s00705-016-2781-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the epidemiology and virology of mild, severe and fatal human infections with avian influenza A (H7N9) virus

Abstract: A novel avian influenza A (H7N9) virus caused 5-10 % mild and 30.5 % fatal human infections as of December 10, 2015. In order to investigate the reason for the higher rate of fatal outcome of this infection, this study compared the molecular epidemiology and virology of avian influenza A (H7N9) viruses from mild (N = 14), severe (N = 50) and fatal (N = 35) cases, as well as from non-human hosts (N = 73). The epidemiological results showed that the average age of the people in the mild, severe and fatal groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Although there were significant differences in death rate, the fatality rate was similar among the last four waves and there was no significant trend in death rate across the five waves. The reason for these similarities in the epidemic characteristics among the five waves may be because the circulating H7N9 virus genotypes were similar to those in previous waves, although there were a few point mutations discovered in the amino acids in some samples, which might increase the virus’ adaptation to gain person-to-person transmission ability and infect humans more efficiently [ 21 23 ]. The conclusion to date was that the genetic changes have not been sufficient enough to alter the antigenic characteristics or cause sustained human-to-human transmission[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were significant differences in death rate, the fatality rate was similar among the last four waves and there was no significant trend in death rate across the five waves. The reason for these similarities in the epidemic characteristics among the five waves may be because the circulating H7N9 virus genotypes were similar to those in previous waves, although there were a few point mutations discovered in the amino acids in some samples, which might increase the virus’ adaptation to gain person-to-person transmission ability and infect humans more efficiently [ 21 23 ]. The conclusion to date was that the genetic changes have not been sufficient enough to alter the antigenic characteristics or cause sustained human-to-human transmission[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results on a study of E627K and D710N mutations in PB2 of H7N9 viruses have also been observed by Zhu et al [ 103 ]. Recent epidemiologic study analyzed that E627K in PB2, R294K in NA and V100A in PA mutations were markedly associated with an increased fatality rate in humans [ 104 ]. Recently, in a study by Qi et al [ 105 ], mutations E627K and K526R in PB2 were found in three of the four human H7N9 HPAIVs, which are also associated with mammalian adaptation similarly observed in H5N1 [ 89 ].…”
Section: Avian Influenza Virus Transmission In Various Mammalsmentioning
confidence: 99%
“…Such evolution has been observed in a fatal human case of influenza A/H7N7 (Jonges et al, 2014) and in mouse experiments following serial lung passage using an isolate from this outbreak (de Jong et al, 2013). Lys at position 627 has also been associated with greater severity in zoonotic H7N9 (Sha et al, 2016) and H5N1 (de Jong et al, 2006) cases However, reverse genetics experiments show that certain strains of avian influenza may be less able to accept these mutations than others (Long et al, 2013). …”
Section: Trait 3: Polymerase Complex Efficiencymentioning
confidence: 99%
“…It also indicates that not all the human-adaptive changes must be in place in the avian reservoir to initiate this process. Some human infections, including some zoonotic cases (de Jong et al, 2006; Chen et al, 2014, 2006; Sha et al, 2016) and some cases early in a pandemic (Rogers and D'Souza, 1989; Connor et al, 1994; Stevens et al, 2006; Glaser et al, 2005; Pappas et al, 2010), involve viruses that are not yet fully human-adapted (see below and Tables 2–4). The interpretation of some of these isolates is complicated by uncertainty about whether they were passaged in hen’s eggs at some point in their history.…”
Section: Introductionmentioning
confidence: 99%